Strong Character From The East: Traces Of Pancasila and Papuan Culture in Student Sports - Haeruddin Azhari; Yorman; Muhammad Teguh Prasetyo; Muharis; Hamzah Hamzah; Khumaira Marsyahidah Badu; M. Azy' Ari (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This study examines the role of Pancasila values and local Papuan culture in shaping the character of sports students at Cenderawasih University, particularly in strengthening moral, social, and cultural integrity amid globalization challenges. A descriptive quantitative approach was employed, involving 29 students from the Sports Education Study Program selected through purposive sampling. Data were collected using a four-point Likert scale questionnaire covering indicators of Pancasila values (belief in God, humanity, unity, democracy, and justice) and Papuan cultural values (solidarity, togetherness, respect for customs, and collective courage). Data analysis utilized percentage techniques with descriptive classification criteria. The findings reveal that all indicators fall within the outstanding category, with average scores ranging from 84% to 92%. These results indicate that students have successfully internalized values such as religiosity, empathy, cooperation, sportsmanship, fairness, and respect for tradition in both academic and athletic contexts. The study confirms that integrating Pancasila and Papuan cultural values significantly contributes to the development of resilient, ethical, and identity-driven sports students. Therefore, higher education institutions are encouraged to systematically embed these values into curricula, instructional strategies, and extracurricular programs to produce graduates who are not only academically and physically competent but also morally grounded and socially responsible in a globalized world.